Voice Command-Based IoT on Smart Home Using NodeMCU ESP8266 Microcontroller - Muhammad Ariel Shakaramiro; Aris Gunaryati; Ben Rahman (LPPM Universitas Islam 45 Bekasi, 2024)
This research focuses on developing a Smart Home prototype that integrates the Internet of Things (IoT) and voice command using the NodeMCU ESP8266 microcontroller. This system allows users to control household devices such as lights, gates, and fans with voice commands through voice-enabled devices. The prototype utilizes NodeMCU ESP8266 to connect the devices to a WiFi network. The developed voice recognition system can accurately identify voice commands and send instructions to NodeMCU ESP8266 to control the corresponding devices. The test results demonstrate the prototype's efficiency in automating household devices through voice commands. Consequently, users can enhance comfort and energy efficiency within their homes. This research opens opportunities for the development of smarter and user-friendly Smart Home systems in the future. Response testing of the Blynk application showed a 100% success rate, with an average response time of less than ten seconds. WiFi network testing was carried out with the IP Address 192.168.101.137, resulting in good functional performance even in the presence of physical obstacles, and the device can operate well up to a distance of 22 meters.